2019
DOI: 10.1101/872093
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Higher Proportion of Craniosynostosis Genes Are Cancer Driver Genes

Abstract: Craniosynostosis (CRS) is a congenital abnormality deformity with a heterogenous genetic contribution. Previously, there are two attempts to collect genes that are genetically associated with craniosynostosis and some related syndromes with 57 (Twigg and Wilkie, 2015) and 39 (Goos and Mathijssen, 2019) genes identified, respectively. We expanded this list of craniosynostosis genes by adding another 17 genes with an updated literature search. These genes are shown to be more likely to be intolerant to functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 143 publications
0
1
0
Order By: Relevance
“…Based on the current state of knowledge, researches on miRNAs in craniosynostosis are scanty. However, Misra et al stated that transcription factors and microRNA are associated with craniosynostosis ( Misra et al, 2019 ). Through Bioinformatics prediction and RIP analysis, we found that HOTAIR could directly combine with miR-152.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the current state of knowledge, researches on miRNAs in craniosynostosis are scanty. However, Misra et al stated that transcription factors and microRNA are associated with craniosynostosis ( Misra et al, 2019 ). Through Bioinformatics prediction and RIP analysis, we found that HOTAIR could directly combine with miR-152.…”
Section: Introductionmentioning
confidence: 99%